A Multi-Institutional Experience in Pediatric High-Grade Glioma - Walston, Steve; Hamstra, Daniel A.; Oh, Kevin; Woods, Gary; Guiou, Michael; Olshefski, Randal S.; Chakravarti, Arnab; Williams, Terence M. (Frontiers in Oncology, 2015)
ABSTRACT Introduction Pediatric high grade gliomas are rare tumors with poor outcomes and incompletely defined management. We conducted a multi-institutional retrospective study to evaluate association of clinical, pathologic, and treatment characteristics with outcomes. Materials and methods Fifty-one patients treated from 1984-2008 at Ohio State University or University of Michigan were included. Histologic subgroups were compared. Log-rank and stepwise Cox proportional hazard modeling were used to analyze progression-free survival (PFS) and overall survival (OS) within the whole group, grade III subgroup, grade IV subgroup, and subtotal resection/biopsy subgroup. Results Median OS was 27.6 months. Grade III histology, complete tumor resection, and cerebral tumor location correlated with improved PFS and OS. Temozolomide use and chemotherapy after radiotherapy or chemoradiation were associated with better PFS while seizure at presentation was associated with better OS. In multivariate analysis, complete resection and chemotherapy following radiotherapy or chemoradiation were independent predictors for improved PFS and OS. For grade III and IV subgroups, complete resection was associated with improved OS (grade III) and seizure presentation was associated with improved OS (grade IV). In the incompletely resection subgroup, temozolomide use and concurrent chemoradiation independently correlated with improved PFS, while higher radiation dose (≥ 59.4 Gy), and adjuvant chemotherapy were independently associated with improved OS. Discussion Total resection and receiving chemotherapy adjuvant to radiation or chemoradiation are most closely associated with improved PFS and OS. For higher risk incompletely-resected patients, temozolomide use and treatment intensification with concurrent chemoradiation, adjuvant chemotherapy, and higher radiation dose were associated with improved outcomes.